2008
DOI: 10.1291/hypres.31.59
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Renin-Angiotensin-Aldosterone System Triple Blockade on Non-Diabetic Renal Disease: Addition of an Aldosterone Blocker, Spironolactone, to Combination Treatment with an Angiotensin-Converting Enzyme Inhibitor and Angiotensin II Receptor Blocker

Abstract: Although dual blockade of the renin-angiotensin-aldosterone system (RAAS) with the combination of an angiotensin-converting enzyme inhibitor (ACE-I) and angiotensin II receptor blocker (ARB) is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
1
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(69 citation statements)
references
References 59 publications
(60 reference statements)
2
62
1
2
Order By: Relevance
“…Blockade of the MR has been demonstrated to have a general renoprotective effect in patients with diabetes mellitus (27,28,29,30) and with chronic kidney disease (31,32,33) as indicated by a reduction of proteinuria. Although aldosterone excess as in PA is known to cause additional deleterious effects on the kidney (34), there are only a few studies investigating effectiveness of PA therapy on renal function.…”
Section: Discussionmentioning
confidence: 99%
“…Blockade of the MR has been demonstrated to have a general renoprotective effect in patients with diabetes mellitus (27,28,29,30) and with chronic kidney disease (31,32,33) as indicated by a reduction of proteinuria. Although aldosterone excess as in PA is known to cause additional deleterious effects on the kidney (34), there are only a few studies investigating effectiveness of PA therapy on renal function.…”
Section: Discussionmentioning
confidence: 99%
“…In an open-label, multicenter, prospective controlled study involving 32 patients with nondiabetic CKD and persistent proteinuria, Furumatsu et al 33 compared the treatment of SPL to trichlormethiazide or furosemide. After 1 year of treatment, proteinuria was reduced by 58% in the SPL group but did not change significantly in the control group.…”
Section: Nondiabetic Chronic Proteinuric Nephropathymentioning
confidence: 99%
“…Eight studies included diabetic patients; the large study of Bianchi et al included patients with various forms of glomerulonephritis (23); the remaining two studies included patients with nondiabetic renal disease encompassing IgA nephropathy, benign nephrosclerosis, and membranous nephropathy (35,36). All studies excluded patients with GFR Ͻ30 ml/mim/1.73m 2 .…”
Section: Trial Characteristicsmentioning
confidence: 99%
“…Bianchi et al reported that six out of 83 patients developed gynecomastia (only one patient warranting discontinuation of medication and five patients with mild gynecomastia) in the spirinolactone group but none (out of 82 patients) in the placebo arm (23). Furamatsu et al reported one of 15 patients who developed gynecomastia in the spironolactone group that did not require discontinuation of therapy (35).…”
Section: Gynecomastiamentioning
confidence: 99%